2018
DOI: 10.5194/hess-2018-78
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Practical experience and framework for sensitivity analysis of hydrological models: six methods, three models, three criteria

Abstract: Abstract. Sensitivity Analysis (SA) and Uncertainty Analysis (UA) are important steps for better understanding and evaluation of hydrological models. The aim of this paper is to briefly review main classes of SA methods, and to presents the results of 10 the practical comparative analysis of applying them. Six different global SA methods: Sobol, eFAST, Morris, LH-OAT, RSA and PAWN are tested on three conceptual rainfall-runoff models with varying complexity: (GR4J, Hymod and HBV) applied to the case study of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Rathod and Manekar [37] identified that the imperviousness of the catchment area is the least influencing parameter. According to Wang and Solomatine [58], the time to peak is the most influential model parameter, while Ghumman et al [1] observed that the kinematic wave parameter is the most contributing hydrologic element in rainfall runoff modeling. This discussion shows that it is wise to perform a sensitivity analysis of hydrologic model parameters for each catchment in order to achieve better understanding of rainfall-runoff behavior.…”
Section: Discussion On Results (Comparison With Other Research Work)mentioning
confidence: 99%
“…Rathod and Manekar [37] identified that the imperviousness of the catchment area is the least influencing parameter. According to Wang and Solomatine [58], the time to peak is the most influential model parameter, while Ghumman et al [1] observed that the kinematic wave parameter is the most contributing hydrologic element in rainfall runoff modeling. This discussion shows that it is wise to perform a sensitivity analysis of hydrologic model parameters for each catchment in order to achieve better understanding of rainfall-runoff behavior.…”
Section: Discussion On Results (Comparison With Other Research Work)mentioning
confidence: 99%
“…We varied the four parameter β , Smax, FCfrac and kres within a defined limits (Table 3) using the shuffled complex evolution SCE-UA (Duan et al, 1994) uniform sampling scheme. The parameter ranges were defined in close accordance with other 235 studies (Beck et al, 2016;Osuch, 2015;Piotrowski et al, 2017;Wang and Solomatine, 2018).…”
Section: ) 230mentioning
confidence: 60%